SENSE OF COHERENCE ON LIQUOR ABUSE AMONG TEENAGERS IN SALUTOGENESIS CONTEXT - Oedojo Soedirham; Verdian Nendra Dimas Pratama (Jurnal Ners, 2014)
Introduction: Liquor abuse in Indonesia, especially among teenagers is now a public health problem that is quite alarming even been able to say ‘red lights.’ Impact of follow such behavior is increasing deviation forms such as delinquency, fights, the emergence of juvenile gangs, acts immoral, and rampant thuggery in teenagers.Methods: Type in this study was a descriptive cross-sectional with a purposive sample collection methods. Nonetheless applied inclusion criteria to be getting more specifi c respondents.Results: The results showed that the teens did not have a positive life orientation evidenced by the majority of them do not want to change and do not know whether to change or not. The attitude may be due to the infl uence of a very strong group.Conclusion: Based on the 29 SOC questions concluded that on average the respondents did not want to turn in because of stress. “Sense of coherence” is a formulation provides a theoretical explanation for the central role of stress in human functioning. The pressures of life signifi cantly reduces the belief that the world is understandable, meaningful, and manageable, and can lead to psychological distress. Thus, a sense of coherence is also a mediator of the effects of life stress on mental health.